2018
DOI: 10.1111/jam.13922
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and kinetic studies of lignin degrading enzymes ofGanoderma boninenseby naturally occurring phenolic compounds

Abstract: The study has shed a light towards a new management strategy to control basal stem rot disease in oil palm. It serves as a replacement for the existing chemical control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Growth suppression of G. boninense by 150 parts per million (ppm) (which is approximately 1 mM), or higher concentrations of SA, accompanied by mycelial growth recovery was previously documented [24]. The growth of G. boninense was also found to be completely inhibited on media containing 5 mmol benzoic acid (the precursor of SA) or SA, while the addition of 1 mmol SA inhibited MnP and Lac up to 72 and 64% [23]. Although we found that 1 mM SA could decrease the mean values of MnP and Lac enzyme activities in SA-treated G. boninense, the decreases were shown to be non-significant.…”
Section: Sequence Analysis Of Gbmnps and Gblacs In G Boninensementioning
confidence: 76%
“…Growth suppression of G. boninense by 150 parts per million (ppm) (which is approximately 1 mM), or higher concentrations of SA, accompanied by mycelial growth recovery was previously documented [24]. The growth of G. boninense was also found to be completely inhibited on media containing 5 mmol benzoic acid (the precursor of SA) or SA, while the addition of 1 mmol SA inhibited MnP and Lac up to 72 and 64% [23]. Although we found that 1 mM SA could decrease the mean values of MnP and Lac enzyme activities in SA-treated G. boninense, the decreases were shown to be non-significant.…”
Section: Sequence Analysis Of Gbmnps and Gblacs In G Boninensementioning
confidence: 76%
“…It was suggested that immunization of OP seedlings with benzoic and salicylic acid under heavy infection pressure reduced BSR development ( Surendran et al, 2018a ). Moreover, ( Surendran et al, 2018b ) and ( Surendran et al, 2018c ) emphasized inhibition of wood degrading enzymes from the fungus to prevent the disease. The environmental impact of using phenolic compounds in the field needs consideration as they are often toxic.…”
Section: Management Of Bsr Diseasementioning
confidence: 99%
“…The degradation of oil palm wood by G. boninense starts when mycelia penetrate the plant cell through an unwounded root and colonize the lower stem of the palm [27]. Successful penetration and further degradation of oil palm wood by G. boninense depend on the production of ligninolytic and hydrolytic enzymes [28,29]. Ligninolytic enzymes are the key to the penetration process through oil palm roots and involvement in the degradation of lignin.…”
Section: Introductionmentioning
confidence: 99%
“…Ligninolytic enzymes are the key to the penetration process through oil palm roots and involvement in the degradation of lignin. These enzymes include two peroxidase enzymes, which are lignin peroxidase (LiP) and manganese peroxidase (MnP) and laccase enzymes [29,30]. The production of these enzymes is essential for G. boninense to penetrate and overcome the first barrier of plant defence, and degradation of lignin is considered to be the rate-limiting step in the infection process [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation